Indonesian clinical practice guidelinesfor systemic and biologic agents for adults with plaque psoriasis - E, Novianto; WK, Budianti; EM, Fitri; BE, Wiryadi; RW, Soebaryo; EHD, Pusponegoro; EH, Effendi; G, Rahmayunita (UI Scholars Hub, 2021)
Background: In response to various biologic and non-biologic systemic agents available in Indonesia, proper and accredited treatment guidelines are required to ensure patient safety. Appropriate treatment is crucial and may affect remission time and morbidities. These guidelines were developed by the Indonesian Society of Dermatology and Venereology – Kelompok Studi Psoriasis Indonesia (INSDV-KSPI) to provide updated decision-making algorithms for the biologic and non-biologic systemic agents for the treatment of adult patients with plaque psoriasis. Methods: Experts from twelve institutions across Indonesia were involved in developing the guidelines. Subsequently, a focus group discussed various journals, researchable questions, eligibility criteria, and outcomes of various treatments options. Results: Modified evidence to decision framework of treatment choices were constructed to aid dermatovenerologists across Indonesia in making a clinical judgment on the size of treatment options of biologic and non-biologic systemic agents for psoriasis treatment in Indonesia. Conclusion: These clinical practice guidelines, accepted and acknowledged by the Indonesian Society of Dermatology and Venereology - Kelompok Studi Psoriasis Indonesia (INSDV-KSPI), have been developed to present the latest and concise evidence- and experience-based guideline targeted towards dermatovenereologists in Indonesia on the management of adult plaque psoriasis.